2011
DOI: 10.1002/jso.21885
|View full text |Cite
|
Sign up to set email alerts
|

TNF dose reduction and shortening of duration of isolated limb perfusion for locally advanced soft tissue sarcoma of the extremities is safe and effective in terms of long‐term patient outcome

Abstract: Dose reduction and shorter duration of TM-ILP seem to be safe and effective regarding long-term patient outcome, as 5-year local control rates and (limb)-survival are not compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In cases of small lesions restricted to the distal parts of the limb, isolated limb infusion with melphalan can be of value 36. Literature suggests that reduction of duration of TM-ILP has no influence on either clinical response or local control 37. However, these results are achieved in soft tissue sarcoma patients and should be investigated in an IT-mets melanoma study population.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of small lesions restricted to the distal parts of the limb, isolated limb infusion with melphalan can be of value 36. Literature suggests that reduction of duration of TM-ILP has no influence on either clinical response or local control 37. However, these results are achieved in soft tissue sarcoma patients and should be investigated in an IT-mets melanoma study population.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, tumor surgery was performed as a shelling‐out procedure with R2 resections in a relevant number of patients. The results at Groningen for 71 patients were much better, with an estimated 5‐year LDFS of 87% achieved by compartment‐oriented resection of the residual tumor . With a similar surgical approach, the estimated 5‐year LDFS was 82% for 90 patients treated at the sarcoma centers of Berlin and Mannheim with TNF‐ILP as a neoadjuvant treatment followed by radical limb‐preserving resection, and the estimated 5‐year metastasis‐free survival rate was 51%, which demonstrated the aggressive behavior of the sarcomas selected for ILP treatment .…”
Section: Oncological Outcome After Tnf‐ilp and Tumor Resectionmentioning
confidence: 94%
“…Currently, most ILP centers do not use rhTNFα dosages greater than 2 mg for the lower extremities or greater than 1 mg for the upper extremities. In the initial trials, melphalan was injected into the limb circuit 30 minutes after rhTNFα, and the cumulative perfusion time was 90 minutes . Hoven‐Gondri et al demonstrated that the perfusion time may be reduced to 60 minutes without the treatment response being compromised. The standard perfusion time is currently 60 to 75 minutes, and melphalan is administered 15 minutes after rhTNFα. The vascular access for establishing the limb circuit is chosen to be as close to the tumor as possible.…”
Section: Current Standards In Tnf‐ilpmentioning
confidence: 99%
“…First, the addition of postoperative EBRT to HILP and delayed surgical resection resulted in a significant improvement in local control without increasing morbidity in ESTS patients . Moreover, a follow‐up study showed that dose reduction and a shorter HILP duration was safe and effective for patient outcome, as the 5‐year local control rates and (limb) survival were not compromised …”
Section: Discussionmentioning
confidence: 99%